(untitled) (International Journal of Medicine and Medical Sciences, 2019)
Ficus religiosa is being used in Ayurvedic and Malay traditional medicine for the treatment of various diseases including gastric ulcer. Considering the above claims, the present work was undertaken to validate the anti-ulcer potential of the ethanol extract of stem bark of F. religiosa against in vivo indomethacin- and cold restrained stress-induced gastric ulcer, and pylorus ligation assays. The extract (100, 200 and 400 mg/kg) significantly (P<0.05) reduced the ulcer index in all assays used. The extract also significantly (P<0.05) and increased the pH of gastric acid while at the same time reduced the volume of gastric juice and, free and total acidities. In conclusion, the present study provide preliminary data on the antiulcer potential of F. religiosa stem bark and support the traditional uses of the plant for the treatment of gastric ulcer.